Instrument-based Tests for Measuring Anterior Chamber Cells in Uveitis: A Systematic Review. (17th August 2020) - Liu, Xiaoxuan; Solebo, Ameenat L.; Faes, Livia; Beese, Sophie; Braithwaite, Tasanee; Round, Matthew E.; Panthagani, Jesse; Kale, Aditya U.; McNally, Thomas W.; Abdulla, Didar; Keane, Pearse A.; Moore, David J.; et al.
ABSTRACT: Purpose: New instrument-based techniques for anterior chamber (AC) cell counting can offer automation and objectivity above clinician assessment. This review aims to identify such instruments and its correlation with clinician estimates. Methods: Using standard systematic review methodology, we identified and tabulated the outcomes of studies reporting reliability and correlation between instrument-based measurements and clinician AC cell grading. Results: From 3470 studies, 6 reported correlation between an instrument-based AC cell count to clinician grading. The two instruments were optical coherence tomography (OCT) and laser flare-cell photometry (LFCP). Correlation between clinician grading and LFCP was 0.66–0.87 and 0.06–0.97 between clinician grading and OCT. OCT volume scans demonstrated correlation between 0.75 and 0.78. Line scans in the middle AC demonstrated higher correlation (0.73–0.97) than in the inferior AC (0.06–0.56). Conclusion: AC cell count by OCT and LFP can achieve high levels of correlation with clinician grading, whilst offering additional advantages of speed, automation, and objectivity.